Fireproof your life : building a faith that survives the flames - Catt, Michael C. (Fort Washington, Pa. : CLC Publications, 2008)
Michael Catt shows how, like the great sequoia, we can stand strong through the fiery trials of life, and even be fruitful. Using illustrations from his own life and from the new movie, FIREPROOF (produced by his congregation, Sherwood Baptist Church), Catt shows eight ways we can prepare our lives for the trials that inevitably come our way. Discussing practical issues such as temptation, marriage and finances, he reminds us that in an eroding culture we are called to stand firm in our faith. Rather than succumb to the pressure of circumstances, we can stand tall and face our challenges in Christ's power. Life's trials can overcome us or they can serve us, growing us into the mature, life-giving believers God intends. - Publisher.
Standing in the fire -- Fireproof your life right now -- Fireproof your faith -- Fireproof your heart and mind -- Fireproof your convictions -- Fireproof your decision-making -- Fireproof your marriage -- Fireproof your finances -- Fireproof for times of conflict and crisis -- Fireproof your life for eternity -- Epilogue : Leaving a legacy.
Author info: Michael Catt, has been pastor of Sherwood Baptist Church in Albany, Georgia since 1989. He counts it a privilege to have been mentored in his early years of ministry by Vance Havner, and helped create a web site, http://www.vancehavner.com, to promote Dr. Havner's writings. He started a web resource for pastors, http://www.2ProphetU.com with Dr. Warren Wiersbe and is the founder of ReFRESH, http://www.ReFRESHConference.org, a conference on revival. He and his wife Terri have two children, Erin and Hayley. - Publisher.
Keywords: Christian life; Christian life